Prediction Markets, the True Value of the Revolving Door and the US Cabinet - Benjamin Koch; Simon Luechinger; Christoph Moser (CESifo GmbH, 2024)
We estimate the value of the revolving door for firm executives and directors joining the cabinets of the Trump I and Biden administrations. By combining intraday stock and prediction market data, we take the degree of anticipation of political appointments into account and we offer estimates for the true value of the revolving door. Following nominations, stock prices and expected appointment probabilities rise strongly for nominees and drop modestly for runners up. Although largely anticipated, prediction markets still move significantly on nomination announcements. For positive jumps in prediction markets, we also find large positive stock price reactions.
Keywords: D73; G14; 330; U.S. Cabinet; revolving door; event study; prediction market; stock market